Strategic Line Drawing between Debt and Equity - Niels Johannesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2011)
Corporate tax systems generally maintain a sharp distinction between debt and equity, however, the advent of hybrid instruments has transformed the universe offinancial instruments into a debt-equity continuum and tax systems therefore need to draw lines that distinguish the set of debt instruments from the set of equity instruments. When countries draw these lines differently, there is a scope for international tax planning: A multinational firm financing a foreign investment with a hybrid instrument categorized as debt in the host country and equity in the home country combines the benfits of tax deductible interest payments in the host country and tax favored dividend payments in the home country. This paper develops a theoretical model of strategic line drawing between debt and equity in the presence of hybrid instruments. In the absence of international cooperation, lines are generally drawn in a globally suboptimal manner. The inefficiency ciency typically derives from the endeavors of policymakers to draw lines in ways that facilitate hybrid financing by domestic multinational firms and impede hybrid financing by foreign multinational firms with a view to eroding foreign taxation of domestic firms and enforcing domestic taxation of foreign firms.
Keywords: 330; Unternehmensbesteuerung; Internationales Steuerrecht; Steuerplanung; Multinationales Unternehmen; Theorie